GAMBARAN KINERJA DAN ETOS KERJA PEREMPUAN SUKU SASAK YANG BEKERJA DI DENPASAR - Viorica, Putu Ayu Novia; Indrawati, Komang Rahayu (Jurnal Psikologi Udayana, 2016)
This research focus on performance and work ethics in Sasak Women. Sasak women have culture and local wisdom that influence their performance and work ethics in workplace.Rasyidi (2008) shows that Sasak women has six values such as leadership, faithfulness, justice, social prosperity, caring with others and tolerance each others. One of the local wisdom in Sasak Women is weave. There are six values in weave fabric ornaments such as Subahnale as patience and sincerity value, Sabuk Peraban as teamwork and kinship value, Sri Menanti as complementary value, Lonong Abang Ragi Genap as perfectness in culture ceremony, Pucuk Rebong as prosperity value, and Bintangan as glory and wealth value (Rosyidi, 2012).This study used qualitative method with phenomenological approach. Goals of this research is to know the representation of performance and work ethics in Sasak women who works in Denpasar. This research shows that performance representation in Sasak women is willing to work in team and individual, caring to supervisor, unadaptable with supervisor regulation, and lack of initiative. Work ethics in Sasak women was perform negatively even they knows that is unhoped for work.Keywords: performance, work ethic, Sasak women